2019
DOI: 10.7573/dic.2019-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy for double-hit lymphoma

Abstract: Double-hit lymphoma (DHL) is a rare type of aggressive B-cell lymphoma defined as a high-grade B-cell lymphoma (HGBCL) with the presence of MYC, BCL2 and/or BCL6 rearrangements. Patients usually present with rapidly progressive and advanced stage of disease and, commonly, with extranodal involvement. Typically, patients become refractory to standard R-CHOP, and more aggressive regimens such as DA-EPOCH-R, R-hyperCVAD or CODOX-R regimens are typically needed. MYC is considered an “undruggable” mutation. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…REPOCH has been used as the standard CIT for DH/TH lymphomas. 9 He responded well-achieving complete remission following anthracycline-based CIT.…”
Section: Discussionmentioning
confidence: 95%
“…REPOCH has been used as the standard CIT for DH/TH lymphomas. 9 He responded well-achieving complete remission following anthracycline-based CIT.…”
Section: Discussionmentioning
confidence: 95%
“…However, our data suggested that the R-DAEPOCH regimen may not overcome haematological toxicity, and treatment for prevention of neutropenia and infection should be provided. The prognosis and outcomes of HGBCL when treated with R-CHOP are worse than those when treated with other regimens, with 5-year PFS and OS rates of approximately 20-30% [19]. Therefore, higher-intensity chemotherapy regimens, such as R-DAEPOCH, R-Hyper-CVAD/MA (rituximab, cyclophosphamide, vincristine, doxorubicin, dexamethasone/methotrexate and cytarabine) and R-CODOX-M/IVAC (rituximab, cyclophosphamide, vincristine, doxorubicin, methotrexate, ifosfamide, etoposide, and cytarabine), have been used for HGBCL patients, although standard of treatment is not established.…”
Section: Discussionmentioning
confidence: 99%
“…At present, no standard treatment protocol has been developed for this disease. 16 Clinical trials are still underway to determine which may confer better progression free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%